Characteristics of the Works of Charles Dickens - Berdiyeva Sitora Utkirovna (European Science Publishing, 2023)
This article talks about the life and literary career of great British writer Charlz Dickens, and his unique style of writing, specific feature of his works.
Keywords: psychological features, character, symbolism, stylistic devices, satire.